Youth identity and postsecondary decision making in a rural state: evidence of a College for All master narrative - Seaman, Jayson; Coppens, Andrew D.; Hartman, Cindy L.; Sharp, Erin Hiley; Jusseaume, Sarah; Donovan, Molly (Frontiers in Education, 2023)
This study examined the normative messages that inform youth postsecondary decision making in a predominantly rural state in the northeastern U.S., focusing on the institutionalization and circulation of identity master narratives. Using a multi-level, ecological approach to sampling, the study interviewed 33 key informants in positions of influence in educational, workforce, and quality of life domains. Narrative analysis yielded evidence of a predominant master narrative -College for All -that participants described as a prescriptive expectation that youth and families orient their postsecondary planning toward four-year, residential baccalaureate degree programs. Both general and domain-specific aspects of this master narrative are elaborated, as well as findings indicating that the College for All ideology appears to both obscure and stigmatize the development and institutionalization of alternative postsecondary pathways. Implications for rural communities, rural mobility, and future research on narratives informing postsecondary options for youth are discussed.